ANALISIS KESIAPAN GURU FIQIH DALAM MENERAPKAN KURIKULUM MERDEKA DI MTs FATHUL HUDA RIMBO ULU - Febi Kurnia Hati; Sukarno; Samsu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Analysis of the Readiness of Fiqih Teachers in Implementing the Merdeka Curriculum at MTs Fathul Huda Rimbo Ulu Tebo.The Merdeka Curriculum is an extensive intrakurikuler learning curriculum. Optimizing content will be more noticeable, allowing students sufficient time to study a subject, as well as improving their abilities and competencies. Teachers can choose various teaching methods so that students’ interests and learning needs can be fulfilled.The objectives of this study are: (1) to determine the level of readiness of Fathul Huda Rimbo Ulu Tebo in facing the implementation of the Merdeka Curriculum; (2) to identify the factors that hinder or support the implementation of the Merdeka Curriculum at MTs Fathul Huda Rimbo Ulu Tebo; and (3) to examine the follow-up actions taken by fiqh teachers in overcoming obstacles in implementing the Merdeka Curriculum at MTs Fathul Huda Rimbo Ulu Tebo.This study uses a qualitative approach with a case study type. The data sources were obtained from primary data through informants, including the head of the madrasah, vice principal for curriculum affairs, fiqih teachers, and students. Secondary data were obtained through observation and documentation. The data analysis techniques used include data collection, data reduction, data presentation, and drawing conclusions.The results of the study show that: (1) the readiness of MTs Fathul Huda in implementing the Merdeka Curriculum is still not optimal, although fiqh subject teachers have the potential to apply it. However, several factors hinder its implementation, such as limited facilities and lack of training or introduction to the Merdeka Curriculum, as not all teachers fully understand or master its application. (2) Several inhibiting factors were identified: first, the quality of human resources (teachers) is still inadequate; second, limited facilities and learning resources, including insufficient infrastructure and teachers’ lack of technological proficiency; third, teachers are already comfortable with traditional teaching methods and lack experience in implementing the Merdeka learning approach. 3) The follow-up actions taken by the school include the head of the madrasah acting as a motivator for teachers by providing encouragement and support to learn the Merdeka Curriculum, along with socialization and training sessions. Workshops on the Merdeka Curriculum are also conducted for teachers, and efforts are made to improve school facilities. Keywords: Readiness, Fiqih Teachers, Merdeka Curriculum